Tubules and donuts: a type VI secretion story - Bönemann, Gabriele; Pietrosiuk, Aleksandra; Mogk, Axel (Molecular microbiology, 2010)
The recently identified type VI secretion systems (T6SSs) are present in many pathogenic proteobacteria and are encoded by a conserved gene cluster. T6SSs contribute to virulence development of various pathogens and are often activated upon contact with target cells. Since the identification of the T6SS, substantial progress has been made at all levels, including gene regulation, its impact on bacterial virulence, the function of effector proteins and the mechanism of secretion. Recent structural and mechanistic studies revealed unique features of the T6SS that distinguish it from other secretion systems. Structural similarities between the T6SS-specific exoproteins Hcp and VgrG and components of the cell-puncturing device of tailed bacteriophages suggest that the T6SSs mimic a bacteriophage machinery to puncture target cell membranes and to translocate effector proteins, representing a novel mechanism of effector delivery. In bacteriophages contraction of the tail sheath, which engulfs the tail tube, causes ejection of the cell-puncturing machinery. The T6SS components VipA/VipB form tubular structures, which might function as tail sheaths by engulfing Hcp proteins. The severing of VipA/VipB complexes by the AAA+ chaperone ClpV is essential for type VI protein secretion and might be linked to VipA/VipB tubule contraction, leading to the export of Hcp and VgrG.
Gesehen am 01.02.2023